A Culture of Burning: Social-Ecological Memory, Social Learning and Adaptation in Australian Volunteer Fire Brigades. Issue 3 (4th March 2021) - Dickson-Hoyle, Sarah; Beilin, Ruth; Reid, Karen
Abstract: While Australian government agencies are increasingly emphasizing the need to "build community resilience" to bushfires, communities in many rural landscapes have a strong history of actively managing fire risk, in particular through involvement in volunteer fire brigades. This paper explores social-ecological memory, social learning, and adaptation in volunteer Country Fire Authority brigades in western Victoria, specifically in the context of planned burning of strategic roadside fire breaks. It examines the relationships between local knowledge, narratives and practices of burning and how these shape volunteer identities, embodying "shared responsibility". Findings show that participation in roadside burning is critical for supporting social learning and ongoing community engagement in fire management. However, changing land uses, social demographics and regulatory processes are negatively impacting local volunteer capacities. While brigades have responded by re-organizing their practices, questions remain as to what extent this constitutes adaptation or transformation connecting to broader landscape-level risk management.